Australia’s Murray-Darling Basin: A Century of Polycentric Experiments in Cross-Border Integration of Water Resources Management - Marshall, G.R.; Connell, D.; Taylor, B.M. (International Journal of Water Governance, 2013)
We respond in this article to scholars having identified a theory-practice gap commonly afflicting applications of integrated water resources management (IWRM) internationally, and thus a need for the concept to be recast according to evidence of how integration of fragmented water management efforts actually occurs. The Murray-Darling Basin (MDB) is employed as a longitudinal case study for this purpose, focusing particularly on its cross-border integration challenges. We frame IWRM as the pursuit of coherent collective action by the multiple enterprises (public, private, civic and hybrid) typically constituting the polycentric public industry involved in managing water resources. We look beyond approaches involving overt coordination to other approaches with potential to contribute towards such coherence. We find that Australian governments are no longer able to overtly coordinate the suite of interdependent enterprises relevant to the success of water management efforts in the Basin. Their success in strengthening coherence or integration in these efforts has come to depend increasingly on their ability to devise governance arrangements capable of catalysing (e.g., by fostering conditions supportive of fruitful competitive rivalry or informal collaborations) the kinds of dynamics through which more of the required integration of management efforts emerges on a self-organised basis.